Evaluating Accessibility of Medical Rehabilitation Services in Indonesia: Challenges and Solution - Putra, Muhammad Adib Dwitamma; Lany, Arman (LifeSciFi, 2025)
Limited access and uneven quality of medical rehabilitation services remain major challenges in improving patients’ quality of life in Indonesia. Many patients, especially in remote areas, face difficulties accessing adequate rehabilitation facilities due to limited human and infrastructure resources. Additionally, a lack of public awareness and insufficient psychosocial support reduce therapy adherence. This study aims to evaluate the barriers and potential solutions within Indonesia’s medical rehabilitation system. The research method employs a qualitative descriptive approach using a literature review technique based on secondary data such as scientific articles, policy documents, and relevant research reports. Findings reveal key obstacles including limited facilities, insufficient health insurance coverage for rehabilitation services, and inconsistent service standards across facilities. The discussion highlights the need for strengthening referral systems, improving public health literacy, and developing integrated rehabilitation models that include psychosocial components. The study concludes that enhancing access, service quality, and active participation of patients and families in the rehabilitation process is essential for accelerating recovery and improving patient outcomes.